Balanced Nutrition Education Based on Local Food in the Pregnant Women's Class at the Wonosari Village Assistant Health Center, Tanjung Morawa, Deli Serdang: Edukasi Gizi Seimbang Berbasis Pangan Lokal pada Kelas Ibu Hamil Puskesmas Pembantu Desa Wonosari Tanjung Morawa Deli Serdang - Tetty H. Doloksaribu; Lusyana G. Doloksaribu; Herly Nainggolan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
Wonosari Village is one of the priority locations for stunting prevention with a percentage of pregnant women with chronic energy deficiency of 33.3%, energy intake of 66.7% of the nutritional adequacy rate (RDA), nutritional problems with iron, folic acid, calcium and zinc. Community service activities are carried out to improve the behavior of pregnant women regarding balanced nutrition based on local food. Educational activities are carried out three times, namely once a month in July-September 2023 according to the class schedule for pregnant women. Educational material about stunting, the first 1000 days of life (HPK), and a balanced nutrition guide based on local food (PGS-PL) for pregnant women. Measurement of the mother's level of knowledge about the material presented was carried out before the 1st education (pre-test) and after the 3rd education (post-test) using the interview method using a questionnaire. Pre-test and post-test data analysis was carried out using the Wilcoxon test at α=5%. The results of this community service show a significant increase, the average knowledge score of pregnant women from 7.67 to 10.25 out of a total score of 12. Almost all pregnant women have been able to apply balanced nutrition based on local food based on the type and amount of plate contents. It is hoped that nutrition implementers from the local health center will continue to strengthen the implementation of PGS-PL in every class for pregnant women at the Wonosari Village Assistant Health Center.